A cloud‐based service for emergency evacuation of mine water inrush accidents. (10th December 2020) - Du, Yuanze; Wu, Qiang; Yao, Yi; Zhao, Yingwang; Zhang, Xiaoyan; Hao, Zhichao; Xu, Hua; Du, Zhili
Summary: In a mine water inrush accident, a fast and accurate emergency evacuation response is essential for ensuring the miner's safety. Conventional emergency evacuation response in the mining industry lacks integration of data from monitoring systems and adjustment of the evacuation plan. In this study, a cloud‐based service, named the Cloud EE‐MWI, is proposed for the emergency evacuation for water inrush accidents to support managers in making the best decisions. The Cloud EE‐MWI's architecture consists of three layers, including the information, computation, and visualization layers. Information layer acquires data from monitoring systems and processes the collected data with pre‐saved basic information of the mine to generate a time‐varying network of the accident evolution. The computation layer constructs an workflow to find a reliable water‐avoiding route. The latest departure route algorithm is proposed and the time‐varying earliest arrival algorithm is implemented in parallel on cloud servers to boost the evacuation path planning. Finally, the visualization layer focuses on displaying data from sensors and obtained results from the computation layer on the web‐side. A real case study is investigated to demonstrate that the service can integrate the information of the monitoring systems and support the useful solution of the emergency evacuation.